A semi-analytical algorithm for deriving the particle size distribution slope of turbid inland water based on OLCI data: A case study in Lake Hongze. (1st February 2021) - Lei, Shaohua; Xu, Jie; Li, Yunmei; Li, Lin; Lyu, Heng; Liu, Ge; Chen, Yu; Lu, Chunyan; Tian, Chao; Jiao, Wenzhe
Abstract: The particle size distribution (PSD) slope (ξ) can indicate the predominant particle size, material composition, and inherent optical properties (IOPs) of inland waters. However, few semi-analytical methods have been proposed for deriving ξ from the surface remote sensing reflectance due to the variable optical state of inland waters. A semi-analytical algorithm was developed for inland waters having a wide range of turbidity and ξ in this study. Application of the proposed model to Ocean and Land Color Instrument (OLCI) imagery of the water body resulted in several important observations: (1) the proposed algorithm (754 nm and 779 nm combination) was capable of retrieving ξ with R2 being 0.72 ( p  < 0.01, n = 60), and MAPE and RMSE being 4.37% and 0.22 (n = 30) respectively; (2) the ξ in HZL was lower in summer than other seasons during the period considered, this variation was driven by the phenological cycle of algae and the runoff caused by rainfall; (3) the band optimization proposed in this study is important for calculating the particle backscattering slope (η) and deriving ξ because it is feasible for both algae dominant and sediment governed turbid inland lakes. These observations help improve our understanding of the relationship between IOPs and ξ, which are affected by different bio-optic processes and algal phenology in the lake environment. Graphical abstract: Image 1 Highlights: A new PSD slope estimation algorithm was developed. The algorithm performance for algae or sediment dominant waters was discussed. The spatiotemporal pattern of PSD slope was mapped in Lake Hongze. The response of PSD slope temporal patterns to meteorological data was discussed. Abstract : A new semi-analytical PSD slope estimation algorithm suitable for algae or sediment dominant water was developed.